Introduction and development of Upland cotton cultivars in the Colombian production system: A review - Burbano-Figueroa, Oscar; Montes-Mercado, Karen Sofía; Pastrana-Vargas, Iván Javier; Cadena-Torres, Jorge (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The purpose of this review was to provide a comprehensive description of the Upland cotton cultivars incorporated into the Colombian production systems. Genealogy and traits data of the Colombian cultivars is scattered across grey literature which reduces chances to discover, access and evaluate this information.Consequently, the objectives of this review were: i) to describe traits and genealogy of the Upland cotton cultivars developed by the breeding programs in Colombia, and ii) to describe the Upland cotton cultivars from other countries that have been introduced into the Colombian production system. This data repository is part of the efforts dedicated to consolidate data dispersed in public and private institutions with the purpose of metadata analysis. In the future, this document will provide guidance to procedures of breeding, introduccion of new varieties, and assessment of  the development and introduction of new cultivars on closing yield gaps. Additionally, this review includes recommendations to develop new cultivars based on the current scenario of cotton producers.